Analisis Sosiologi Perempuan Penyadap Karet Single Parent dalam Strategi Bertahan Hidup di Desa Sei Rumbia Kecamatan Kotapinang - Nina Kartika; Neila Susanti; Ahmed Fernanda Desky (Jurnal Pendidikan dan Humaniora Rumbio, 2026)
Living as a single parent, especially as a rubber tapper, is a challenging task. In Sei Rumbia Village, many women work in this profession, including those who are single parents. They juggle two roles, both in the public and domestic spheres. Single-parent rubber tappers are often forced to care for and educate their children alone due to the loss of their husbands through divorce or death. The problem examined in this study concerns the role of single parent female rubber tappers in supporting their families financially. The role of single-parent female rubber tappers in dividing their time between being a housewife and working. This research approach uses a qualitative method. The subjects in this study were five single-parent female rubber tappers aged 50 to 56, who have children and jobs and live in Sei Rumbia Village, Kotapinang District. The research instrument used was in-depth interviews. From the research results obtained that: (1) the role played by single parent female rubber tappers in supporting their family's economy as the backbone, head of the family, and breadwinner from the rubber tapping results. (2) the role played by single parent female rubber tappers in dividing their time between being a housewife and working, namely by waking up early to do all household activities first before they go to work. (3) strategies to face their daily needs, they implement various strategies, namely by working, borrowing money, and hoping for support from family, neighbors and the government.